2005
DOI: 10.1111/j.1365-3164.2005.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of immunostimulatory liposome‐nucleic acid complexes in allergen‐specific immunotherapy of dogs with refractory atopic dermatitis – a pilot study

Abstract: This pilot study evaluated the effects of immunostimulatory liposome-plasmid-DNA complexes combined with specific allergens for immunotherapy of refractory canine atopic dermatitis. Seven dogs with previously diagnosed atopic dermatitis and unsatisfactory response to at least 12 months of conventional allergen-specific immunotherapy underwent a series of six intradermal injections (weeks 0, 2, 4, 6, 10 and 14), with patient-specific allergen extracts contained in cationic liposome-DNA complexes. Degree of prur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
46
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 31 publications
1
46
0
2
Order By: Relevance
“…Other applications of the adjuvant platform include mucosal immunization, where we have found that the liposome-TLR agonist adjuvants are effective (S. Dow, unpublished data). The LANAC adjuvants may also be useful clinically, because we showed recently that vaccination of pet dogs with refractory atopic dermatitis with allergens complexed to LANAC adjuvants was effective in reducing clinical signs and reversing some Th2 abnormalities (71). Therefore, the liposome-TLR agonist adjuvant system described in this study may be a useful addition to the list of currently available vaccine adjuvants capable of eliciting strong T cell responses against protein and peptide Ags.…”
Section: Discussionmentioning
confidence: 98%
“…Other applications of the adjuvant platform include mucosal immunization, where we have found that the liposome-TLR agonist adjuvants are effective (S. Dow, unpublished data). The LANAC adjuvants may also be useful clinically, because we showed recently that vaccination of pet dogs with refractory atopic dermatitis with allergens complexed to LANAC adjuvants was effective in reducing clinical signs and reversing some Th2 abnormalities (71). Therefore, the liposome-TLR agonist adjuvant system described in this study may be a useful addition to the list of currently available vaccine adjuvants capable of eliciting strong T cell responses against protein and peptide Ags.…”
Section: Discussionmentioning
confidence: 98%
“…In other studies in which CpGs were deployed, for example in a study on asthma in humans,20 and a study on dogs with atopic dermatitis,21 CpGs were used as adjuvants for an allergen‐specific immunotherapy or as vaccine adjuvants for increased effectiveness of the human hepatitis B11 and the equine influenza and Rhodococcus equi vaccines 22, 23, 24, 25. In these studies, the CpGs induced a strong Th1 cell‐mediated and humoral immune response 11.…”
Section: Discussionmentioning
confidence: 99%
“…As an adjuvant, CpG‐ODN has been successfully used both in a human phase I and IIa in vivo asthma study with the house dust mite allergen as well as in a study of atopic dogs with specific allergens as an allergen‐specific immunotherapy 20, 21. CpG‐ODN also has been applied as an adjuvant in in vitro and in vivo vaccination studies 22, 23, 24, 25.…”
mentioning
confidence: 99%
“…22 In addition, we also reported that LDC could be used as a vaccine adjuvant for immunization of dogs with refractory atopic dermatitis and that immunization with the LDC-based vaccine could reduce clinical signs and suppress the Th2 polarization of the T cells from atopic dogs. 23 In addition, we showed recently that in cancer-bearing dogs, the LDC adjuvant could be used recently to elicit humoral immune responses even in dogs receiving chemotherapy. 24 Others have also reported that liposomes complexed with DNA can be used to produce effective vaccine adjuvants.…”
mentioning
confidence: 99%